Wear surface characteristics study of tribo-materials under palm oil methyl ester added lubricant - Maleque, Md. Abdul; Masjuki, H.H. (Emerald Group Publishing Ltd., 2002)
The wear properties of tribo-materials are strongly influenced by the use of lubricants and their additives. The presence of additive in the lubricating oil causes changes in the material surface characteristics by the formation of protective boundary films which result in increased wear resistance of the mating surfaces. In this investigation, wear tests for a segmented piston ring-plate pair and a ball-plate pair were carried out using a modified universal wear and friction machine with three different percentages of palm oil methyl ester (POME) added to a mineral oil lubricant. The plain mineral-based lube oil was also used for comparison purposes. Experimental results show that the activity of POME on the metal surface is quite remarkable when added to a mineral-based lubricant. Wear of piston ring and ball bearing materials took place by abrasive, corrosive and/or oxidative mechanisms with different concentrations of POME in lubricants. The surface characteristics shown by SEM and EDAX and related phenomena are discussed in this paper.